Back into the wild: establishing a migratory Northern bald ibis Geronticus eremita population in Europe. Issue 1 (20th May 2017) - Fritz, J.; Kramer, R.; Hoffmann, W.; Trobe, D.; Unsöld, M.
Abstract : From the perspective of zoological institutions reintroduction projects offer many possibilities to link conservation and research programmes. An example of the multi‐layered and diverse contributions that zoological institutions in general and, specifically, Vienna Zoo, Austria, can make is the reintroduction of the Northern bald ibis Geronticus eremita in central Europe. The involvement of zoological institutions ranges from the provision of eggs or birds for release trials, to financial and advocacy support, including with government agencies and non‐governmental organizations. Through involvement at a steering level at the coordinative association 'Förderverein Waldrappteam' and as a partner in the EU LIFE+ reintroduction project, Vienna Zoo directly contributes to the shape of the reintroduction project for this Critically Endangered species, and provides much more than technical and infrastructural support. The reintroduction of the Northern bald ibis is broadly in line with the reintroduction guidelines of the International Union for Conservation of Nature. This project provides added benefits not only through its work to prevent the illegal hunting of migratory birds but also the production and dissemination of scientific research. Abstract : Reintroduction projects provide zoological institutions with many possibilities to link conservation and research programmes. Vienna Zoo (Austria) has contributed in multi‐layered and diverse ways to the reintroduction of Northern bald ibis Geronticus eremita in central Europe. Involvement ranges from the provision of eggs or birds for release trials, to financial and advocacy support, including with government agencies and non‐governmental organizations. Through involvement at a steering‐committee level ('Förderverein Waldrappteam') and a partner in the EU LIFE+ project, Vienna Zoo directly contributes to the shape of the programme. This report, at the midterm of a 6 year project, describes the techniques developed for human‐led migrations and the progress made towards establishing three breeding colonies of Northern bald ibis north of the Alps with a tradition of migration to a wintering area in southern Tuscany. This work has also contributed to the prevention of illegal hunting and dissemination of scientific research. (Photo: Pablo Przesang, 2015)